Building Local Leadership for Research Education : Final Report. - Boud, David; Brew, Angela; Dowling, Robyn; Kiley, Margaret; Malfroy, Janne; McKenzie, Jo; Solomon, Nicky; Ryland, Kevin (Office for Learning and Teaching, 2014)
Final report from a project that addressed leadership in research education at faculty and local levels. Research education is facing a number of challenges as it expands, diversifies and is subjected to greater scrutiny and quality control. As a consequence of these challenges skilful leadership is required to work with these changes particularly at the Faculty and School level. A major challenge for academics with local responsibility for research degrees is to see themselves as leaders of research education rather than as processors of applications and allocators of supervision. Using a distributed leadership framework, this project worked with these academics through institutional research education coordinator communities to develop a series of programs, strategies and resources to build their leadership capacity so that they can lead the necessary changes in research education.